Kesiapan Sistem Hukum Indonesia Dalam Transformasi Masyarakat Dari 4.0 Menuju 5.0 - Niru Anita Sinaga; Dwi Atmoko (KRTHA BHAYANGKARA, 2023)
Law and society are two things that are closely related, as Cicero said, "Ubi Societas Ibi Ius" means, where there is society, there is law. The role of law in the transformation of society from 4.0 to 5.0 is very important. Readiness of the legal system: Legal structure, legal substance and legal culture are very important. The transformation is expected to realize orderly, simple and responsive regulations. This is done by adjusting the situation and conditions that occur without abandoning the values held by the Indonesian people. Relying on universal ethics contained in Pancasila and the 1945 Constitution. It is carried out with strategic steps including: Legislation, human resources, institutions, and legal culture so that the goals of the nation and state in the transformation of national, regional and global scales can be realized. The legal system must be able to keep up with technological developments so that the ideal and desired application of the law can be realized. This study discusses: How is the readiness of the Indonesian legal system in the transformation of society from 4.0 to 5.0? by using normative legal research methods (juridical normative).